1999
DOI: 10.1051/apido:19990403
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides and selected elements in soil and honey from Gorski Kotar, Croatia

Abstract: -This research compared the transfer of 137 Cs, 40 K, Ca, Fe, Rb, Sr, Cu, Zn, Pb, Ni, Mn and Cr from soil into honey derived from meadow flora, mixtures of floral and honeydew honey, and honeydew honey from fir and spruce forests in Gorski Kotar, Croatia. Radionuclides were measured by gamma-ray spectrometry, while other element concentrations were measured by X-ray fluorescence (XRF). Transfer factors (T f ) from soils into the studied honey types, expressed as a percentage, are defined as the ratio between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…Tonelli et al (1990) stated that pollen is the best bioindicator for radionuclides because this substrate presented higher radionuclide D r a f t activity under the same conditions when compared to bees and honey. However, in spite of this consideration, the majority of European studies on the presence of different radionuclides carried out in Germany (Bunzl et al 1988;Assmann-Werthmüller et al 1991), France (Devillers et al 2002b), Italy (Panatto et al 2007;Schiuma et al 2015;Meli et al 2016), Croatia (Barišic et al , 1994(Barišic et al , 1999(Barišic et al , 2002Kezić et al 1997) and…”
Section: Radionuclidesmentioning
confidence: 99%
“…Tonelli et al (1990) stated that pollen is the best bioindicator for radionuclides because this substrate presented higher radionuclide D r a f t activity under the same conditions when compared to bees and honey. However, in spite of this consideration, the majority of European studies on the presence of different radionuclides carried out in Germany (Bunzl et al 1988;Assmann-Werthmüller et al 1991), France (Devillers et al 2002b), Italy (Panatto et al 2007;Schiuma et al 2015;Meli et al 2016), Croatia (Barišic et al , 1994(Barišic et al , 1999(Barišic et al , 2002Kezić et al 1997) and…”
Section: Radionuclidesmentioning
confidence: 99%
“…If it is assumed that any hive includes and least 1000 worker-bees and that each of them forage on one thousand flowers per day, the honey produced daily can be considered the outcome of at least one million interactions. In this way, the forage area is effectively sampled for trace elements and the concentration in honey of heavy and transition metals reflecting levels in the forage area (Bariŝić et al, 1999;Hoefel, 1985;Jones, 1987;Kump et al, 1996;Leita et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For bees, the hive is the place from which foragers stage numerous forays during the day and to which the entire forager force returns at dusk. From 1973 through the early 1990s [ 36 , 37 , 48 , 49 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], we capitalized on bees sampling surrounding environments, trapping at the hive, and analyzing samples of pollen, nectar and honey, wax, and even the bees themselves. We later found that bees’ electrostatic charge improves their effectiveness as samplers and modeled particle size attraction as a function of charge for both chemical and biological (microbes/viruses) agents [ 83 , 84 ].…”
Section: Technological Advancements In Bee-based Biosensors/biomonmentioning
confidence: 99%